2017
DOI: 10.1016/j.soard.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission after gastric bypass: a nationwide cohort study with up to 6 years follow-up

Abstract: BACKGROUND Several studies have addressed short-term admission rates after bariatric surgery. However, studies on long-term admission rates are few and population based studies are even scarcer. OBJECTIVE The aim of this study was to assess short and long-term admission rates for gastrointestinal surgery after gastric bypass in Sweden compared to admission rates in the general population. SETTING Swedish healthcare system. METHODS The surgery cohort consisted of adults with Body Mass Index (BMI) ≥35 iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The fact that individuals on sick leave and long-term disability support in the present material reported low HRQoL may also be due to factors related to concurrent illness [ 27 ]. Low educational level is also associated with increased risk for hospital admission after GBP surgery [ 28 ]. However, inferior HRQoL in these groups may also be due to less %EBMIL which present data indicates when comparing the domains in RAND-36 and weight loss since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that individuals on sick leave and long-term disability support in the present material reported low HRQoL may also be due to factors related to concurrent illness [ 27 ]. Low educational level is also associated with increased risk for hospital admission after GBP surgery [ 28 ]. However, inferior HRQoL in these groups may also be due to less %EBMIL which present data indicates when comparing the domains in RAND-36 and weight loss since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported experience of abdominal pain both prior to and after RYGB should be the focus of future studies. An increased need for abdominal surgery during 6 years post RYGB indicates a potential effect of time that needs further exploration (10).…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish register study of 28,331 patients (median follow-up 3.6 years) found an increased risk for hospital admission for gastrointestinal surgery after RYGB (relative risk 8.6). About one in four patients had additional abdominal surgery during 6 years of follow-up (10). In a Danish study, 67.6% of patients contacted health care after RYGB due to symptoms, and 29% had been hospitalized.…”
Section: Prevalencementioning
confidence: 99%
“… 18 20 In a study by Aman et al, 20 female gender made up 78.9% of all 30-day readmissions following bariatric surgery over a two-year period from 2012 to 2013. 21 The present study demonstrates that females made up 55.5% of 30-day readmissions over a two-year period from 2015 to 2017. It is important to note that although female patients continue to make up the majority of 30-day readmissions, this has decreased substantially.…”
Section: Discussionmentioning
confidence: 50%
“…According to Bruze et al, when compared to the general population, female patients continue to exhibit higher all-cause readmission rates even six years following surgery. 21 Prior studies have demonstrated a relationship between independent pre-operative psychosocial factors which affect the likelihood of readmission following bariatric surgery. Such factors have little to do with the surgical procedure itself, and more to do with unrelated demographic characteristics that may not be immediately obvious during pre-operative assessment.…”
Section: Discussionmentioning
confidence: 99%